Peran Agreeableness dan Resolusi Konflik Terhadap Co-parenting Pada Pasangan Dual- Earner - Ramadhani, Ayu Iffah; Setiawan, Jenny Lukito (Universitas Ciputra Surabaya, 2020)
Dual-earner couples are husband and wife who both work. This couple faces challenges in dividing the roles as parents and as workers. To overcome these challenges, they need to work together, one of which is in terms of parenting. This study aims to determine the role of agreeableness, conflict resolution, and the quality of co-parenting on X Hospital staff and their partners in Surabaya. The hypothesis in this study is that there is a significant role of agreeableness and conflict resolution on co-parenting. The subjects of this study were 39 pairs who live in Surabaya. This research is a correlational quantitative research. Data were obtained using the Big Five Inventory (BFI), PREPARE/ENRICH, and The Co-Parenting Relationship Scale. The results of this study indicate that there is a role for agreeableness and conflict resolution on co-parenting (F = 11.79; p < 0.001). Specifically, agreeableness had a significant role in co-parenting (t = 4.838; p < 0.001) and gave an effective contribution of 23.5% while conflict resolution did not play a significant role.